Amyloid Goiter Secondary to Ulcerative Colitis - Bunyamin Aydin; Yavuz Savas Koca; Tugba Koca; Ihsan Yildiz; Sevda Gerek Celikden; Metin Ciris (Case Reports in Endocrinology)
Diffuse amyloid goiter (AG) is an entity characterized by the deposition of amyloid in the thyroid gland. AG may be associated with either primary or secondary amyloidosis. Secondary amyloidosis is rarely caused by inflammatory bowel diseases. Secondary amyloidosis is relatively more common in the patients with Crohn’s disease, whereas it is highly rare in patients with ulcerative colitis. Diffuse amyloid goiter caused by ulcerative colitis is also a rare condition. In the presence of amyloid in the thyroid gland, medullary thyroid cancer should be kept in mind in the differential diagnosis. Imaging techniques and biochemical tests are not very helpful in the diagnosis of secondary amyloid goiter and the definitive diagnosis is established based on the histopathologic analysis and histochemical staining techniques. In this report, we present a 35-year-old male patient with diffuse amyloid goiter caused by secondary amyloidosis associated with ulcerative colitis.